Antioxidant Activity of Methanol and Chloroform Extracts of Avocado Seeds (Persea americana Mill.) using the DPPH Method - Pratiwi, Ambar; Nafisa, Adilla Shafa (JUPE : Jurnal Pendidikan Mandala, 2023)
One part of the avocado (Persea americana Mill.) that is often unused and considered waste is the avocado seed. Avocado seeds have the potential to be made into an extract because they contain antioxidant compounds. The aim of this research was to determine the highest antioxidant activity, total phenolic and total flavonoid content in methanol and chloroform extracts, and to determine the relationship between total phenolic and total flavonoid content on the IC50values of methanol and chloroform extracts. Antioxidant activity was tested using the DPPH method. Data analysis used the classic assumption test, independent sample t-test, and Pearson correlation test. The results showed that the highest IC50 was found in the chloroform extract at 349.28 ± 137.29 µg/mL DW. The highest phenolic content was found in the methanol extract at 2,419.51 ± 389.54 mgGAE/g DW. The highest total flavonoid content was found in the chloroform extract at 232.13 ± 54.32 mgQE/g DW. Based on the Pearson correlation test, the total flavonoid content had a correlation (0.028<0.05) with the IC50 value of methanol and chloroform extracts of avocado seeds, while the total phenolic content had no correlation (0.749>0.05) with the IC50 value of methanol and chloroform extracts of avocado seeds